0201 Time Of Day Effects On Sleep, Fatigue, And Sleepiness Inflight, Layover, And Post-flight In Short And Long Haul Commercial Aviation Routes. (12th April 2019) - Lamp, Amanda; Gregory, Kevin; Cook, Maxwell; Smith, Rhiannon Soriano; Rasmussen, Ian; Gage, Natasha; Flynn-Evans, Erin; Belenky, Gregory
Abstract: Introduction: Federal Aviation Administration (FAA), 2013 Federal Aviation Regulation (FAR) 14 CFR Part 117.7 allows a data collection enabled alternative to the current prescriptive regulations. Flights under this alternative approach must maintain an "equivalent level of safety" to operations within the current regulations, assessed through Safety Performance Indicators (SPIs) such as sleep, fatigue, and sleepiness. As pilots cross multiple time zones, circadian misalignment is a primary factor affecting SPIs. Methods: Time of day, as a proxy for circadian phase, and sleep duration were measured using actigraphy and sleep/work logbooks, fatigue using the self-report Samn-Perelli Fatigue Scale, and sleepiness using the self-report Karolinska Sleepiness Scale. These SPIs were measured in multiple domestic, long-range (LR), and ultra long-range (ULR) operations. Results: Landing pilot's data (n=640) showed self-reported ratings of fatigue and sleepiness were highest when top of descent occurred during home base time (HBT) nighttime hours (2200-0600) and were lowest in the afternoon/early evening hours (1400-2200). This trend was also found with 76 pilots flying both daytime and nighttime domestic trips and 20 pilots flying a 3-segment overnight trip. LR and ULR trip data (n=92) demonstrated that pilots do not have a set sleep pattern during layovers. Post trip timing of sleep demonstrated pilots sleep during the local night when they return to HBT. Conclusion: Our data indicate that reduction in alertness and increase in fatigue occur when flying during the biological night, relative to HBT. Therefore, the dominant factor to consider when preparing for, executing, and recovering from trips is timing of sleep in relation to the physiological night to maximize sleep. To mitigate the reduction in alertness and increase in fatigue that occurs when flying during the biological night, relative to HBT, we recommend pilots sleep as much as possible during the HBT window of circadian low (WOCL) (0200-0600) and mini-WOCL (1500-1700) and to otherwise "sleep when sleepy, " striving for a minimum of 8 hours sleep per 24 hours. Support (If Any): United Airlines, NASA System-wide Safety Assurance Project